PERAN MEDIA DAKWAH DALAM PEMBANGUNAN MANUSIA - Abdul Manaf (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2018)
In human development process, media is needed which will be a channel in the da'wa carried out. Da'wa as an effort to build the existence of human beings is an entry point that supports the success of it. The more suitable the da'wah media used, the more positive and successful the da'wah will be. Conversely, if the preacher is wrong in choosing a channel causing his missionary activity to fail. This brief article highlights the importance of the media as a missionary channel. The results of the analysis in this paper state that mass media as a da'wah channel has positive implications as a da'wa channel. In addition, mass media also has a negative contribution if it is not maximized by its use and errors in the selection of themes in da'wa.****Dalam pembangunan manusia dibutuhkan media yang akan menjadi saluran dalam dakwah yang dilakukan. Dakwah sebagai upaya membangun keberadaan diri manusia menjadi sebuah entry point yang mendukung keberhasilan terhadapnya. Semakin sesuai media dakwah yang digunakan, maka akan memberikan makna positif dan keberhasilan atas dakwah yang dilakukan. Sebaliknya, apabila pendakwah salah dalam memilih saluran menyebabkan aktivitas dakwahnya menjadi gagal. Tulisan singkat ini menyoroti tentang pentingnya media sebagai saluran dakwah. Hasil analisa dalam tulisan ini menyatakan bahwa media massa sebagai saluran dakwah mempunyai implikasi positif sebagai saluran dakwah. Selain itu media massa juga mempunyai kontribusi negatif apabila tidak dimaksimalkan penggunaannya dan kesalahan dalam pemilihan tema dalam dakwah.